A Sustainable City: A Parallel Diplomacy Study of Bandung towards Kawasaki in Handling Carbons Emissions - Laoli, Rosania; Dermawan, Windy (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2025)
Global climate change has increased the earth's temperature and carbon emissions, including in Bandung City, which now has moderate air quality. In response, Bandung City Government seeks to reduce carbon emissions through various steps, including parallel diplomacy with international parties such as Kawasaki City. This research uses the concept of parallel diplomacy and approaches qualitative methods through descriptive analysis methods. The results show that carbon emissions in Bandung City have been relatively high in the last five years. Handling efforts are carried out by involving foreign cooperation, especially with Kawasaki City, which has been established for a long time through various environmental programs, including carbon emission reduction. However, in its implementation, Bandung City's parallel diplomacy still refers to Indonesian law. In conclusion, Bandung-Kawasaki's parallel diplomacy runs quite well when many actors are involved. However, there are challenges due to differences in the two cities' structure and stages of diplomatic governance.